Understanding of teachers on thematic approach to Malay language in primary schools - Norliza Ramlan; Wan Muna Ruzanna Wan Mohammad; Zamri Mahamod (Journal of Education and Learning (EduLearn), 2026)
In ensuring an effective and successful teaching session, teachers must be wise in selecting teaching approaches that meet the needs of students in this age of information evolution. The thematic approach is one of the methods that offers engaging and realistic learning. Therefore, the main objective of this study is to explore teachers’ understanding of the thematic approach in the Malay language subject for primary schools. This qualitative study used a case study approach, specifically a multi-location case study. The study participants consisted of 5 Malay language teachers from 5 primary schools located in 5 different states in Malaysia. Data collection methods included interviews, observations, and document analysis, with the data analyzed thematically using Nvivo14 software. The findings of the study show that Malay language teachers are able to describe the features of the thematic approach in detail, indicating a strong understanding of the thematic approach. The results also show that Malay language teachers are capable of effectively applying the thematic approach in their teaching and learning sessions. This proves that primary school Malay language teachers are well-prepared in terms of understanding the implementation of the thematic approach in schools. In conclusion, empowering teaching and learning through the thematic approach can ensure the effective delivery of knowledge and language skills. Furthermore, to enhance the application of the thematic approach in improving teachers’ pedagogical practices, future studies could explore the effectiveness of the thematic approach in both teaching and student learning.